2007
DOI: 10.1152/ajprenal.00141.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early postnatal hypernutrition on nephron number and long-term renal function and structure in rats

Abstract: September 26, 2007; doi:10.1152/ajprenal.00141.2007.-Various antenatal events impair nephrogenesis in humans as well as in several animal models. The consecutive low nephron endowment may contribute to an increased risk for cardiovascular and renal diseases in adulthood. However, little knowledge is available on the influence of the postnatal environment, especially nutrition, on nephrogenesis. Moreover, the consequences of early postnatal nutrition in late adulthood are not clear. We used a model of early pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 34 publications
4
70
0
2
Order By: Relevance
“…Overfeeding of normal birth weight rats also had adverse effects. [26][27][28] In line with these findings, we observed that lower fetal weight gain and lower early infancy weight gain led to impaired kidney growth, whereas only lower fetal weight gain led to impaired kidney function. The results from our present study suggest that both fetal life and early infancy may be critical periods for the development of kidney diseases in later life.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneysupporting
confidence: 84%
“…Overfeeding of normal birth weight rats also had adverse effects. [26][27][28] In line with these findings, we observed that lower fetal weight gain and lower early infancy weight gain led to impaired kidney growth, whereas only lower fetal weight gain led to impaired kidney function. The results from our present study suggest that both fetal life and early infancy may be critical periods for the development of kidney diseases in later life.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneysupporting
confidence: 84%
“…The lack of effect on nephron endowment may result from a relative resistance of the IUGR kidney to postnatal nutrition and the end stage of nephrogenesis at which pups were exposed to HP diet. In rodents, in which nephrogenesis begins at midgestation and continues after birth up to days 7-10, neonatal environment, especially nutrition, can influence nephron endowment (23,24). As compared with normal birth weight (NBW) offspring, early neonatal overfeeding fails to improve postnatal nephrogensis in IUGR pups; this is due in part to impaired development of nephron progenitors cells (13,25).…”
Section: Discussionmentioning
confidence: 99%
“…The number of glomeruli per kidney was determined in the two groups of rats on D18 and D160, as previously described (23). Whole kidneys were briefly incubated in a 50% hydrochloric acid solution for 30 to 45 min at 37 °C, the incubation time being dependent on kidney weight.…”
Section: Morphometric Measurements and Estimation Of Nephron Number mentioning
confidence: 99%
“…When LBW rats were overfed post-natally, nephron numbers remained low, and they developed obesity, hypertension and renal injury with time 74 . In post-natally overfed NBW rats, despite a higher than normal nephron number, blood pressure, proteinuria and glomerulosclerosis were all increased in adulthood 75 .…”
Section: Impact Of Childhood Weight Gain On Risk Factors For Chronic mentioning
confidence: 92%